Solution Properties of Low Charge Density Amphoteric Terpolymers via Aqueous Dispersion Polymerization - LIU, HAN-LEI; WU, YU-MIN; XU, JUN; ZHAO, WEN-PENG (Asian Journal of Chemistry, 2010)
Solution properties of low-charge-density ampholytic terpolymers (amPAM) of acrylamide (AM), acrylic acid (AA) and 2-methyl acryloylxyethyl trimethyl ammonium chloride (DMC) prepared via freeradical dispersion polymerization and poly(2-methylacryloylxyethyl trimethyl ammonium chloride) (PDMC) as cationic polymeric stabilizer in the aqueous ammonium sulfate media (D-amPAM) were studied with the reduced viscosities and hydrodynamic radii by variation of the polymer concentration, salt concentration and type and temperature. In D-amPAM solutions, it is found that the influences of hydrogen bonds, the relationships between PDMC and amPAM chains, the microenvironmental salt concentrations around the polymer chains, typically the network structures formed by the effects of salt (Mg2+) and PDMC chain bridges and microaggregation in the solution played important roles which directly relieved the transitions of polymer chain conformation. And the linear manner of the reduced viscosities was different and complicated as a function of the D-amPAM concentrations in different concentration of NaCl media or at different temperature conditions. In concentrated solutions, the data of apparent viscosities and apparent phenomena indicated that the phase-separation behaviors (solution and swollen phases) occured when the D-amPAM concentrations exceeded 1.92 g/dL and the solutions exhibited typically pseudoplastic viscosity profiles.